Effects of Intervention of Street Vendors on Public Spaces of Tegalega Park, Bandung, Indonesia - Irwan, Sudarisman; Muhizam, Mustafa; Mohd Hafizal, Mohd Isa (International Journal of Property Sciences (E-ISSN: 2229-8568), 2019)
The intervention of street vendors to urban public space brings various negative impacts, in addition to positive impacts on the economy. This problem is more complicated and difficult to obtain solution when the number of street vendors who occupy the public space gets bigger. This phenomenon is very visible in the Tegalega Park in Bandung which has an area of 16 hectares and is the largest park in the city of Bandung. Based on a research conducted in 2014 by Indonesian University of Education (UPI) and Bandung city Bappeda the number of street vendors in four areas of Cicadas, Tegalega, Sukajadi, and Burangrang amounted to 9,118 traders. Knowledge about the effects from the presence of street vendors in Tegalega Park is important as a consideration factor in planning the design of public spaces (park) in the future so as to anticipate the problems that may arise. The documentation and analysis of activities within the park which are grouped into non-commercial activities (leisure, play and exercise) and commercial activities (trade) are used as a tool to determine the effects. The results showed that the presence of street vendors' activity led to the formation of different patterns of zoning activity compared to the initial planning of zoning of park activity.